2002
DOI: 10.1088/1126-6708/2002/03/019
|View full text |Cite
|
Sign up to set email alerts
|

Induced Gravity on RS Branes

Abstract: It is shown that a localized four-dimensional Einstein term, induced by quantum corrections, modifies significantly the law of gravity in a Randall-Sundrum brane world. In particular, the short-distance behavior of gravity changes from five-to four-dimensional, while, depending on the values of parameters, there can be an intermediate range where gravity behaves as in five dimensions. The spectrum of graviton fluctuations around the brane, their relative importance for the gravitational force, and the relevanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 35 publications
7
119
0
Order By: Relevance
“…The presence of the four-dimensional curvature scalar in the gravitational action does not affect the bulk equations. If we define 9) then eq. (2.6) reduces to [15] 11) where C is an integration constant, giving the mass of the bulk black hole.…”
Section: Jhep10(2003)066mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the four-dimensional curvature scalar in the gravitational action does not affect the bulk equations. If we define 9) then eq. (2.6) reduces to [15] 11) where C is an integration constant, giving the mass of the bulk black hole.…”
Section: Jhep10(2003)066mentioning
confidence: 99%
“…The solution is the Friedmann equation of the induced gravity model [4,9,10,11] 19) [The ± sign is independent of that in eq. (2.…”
Section: Jhep10(2003)066mentioning
confidence: 99%
“…In ktt [5] the cosmological brane-bulk energy exchange processes , due to KK gravitons were studied in the simplest RS cosmological evolution supplemented with a four-dimensional (induced) Einstein term on the brane . It was shown that, in agreement with intuition, such processes do not affect the cosmological evolution during 4d eras (H ∼ √ ρ), while they are important in higher-dimensional eras (H ∼ ρ).…”
Section: Introductionmentioning
confidence: 99%
“…This fact can be used for explaining the acceleration of the universe [20]. Newton law with 4d induced gravity in the AdS 5 background is also examined [21,22] bulk with the induced Einstein term is the fact that the coupling constant of the δ-function potential is dependent on energy(or mass) as following:…”
mentioning
confidence: 99%
“…If we adjust our conventions with those of Ref. [21], the relation between them is simplŷ Newton potential localized on the brane is generally obtained from the space-time dependent Green function as following [7,19] V ( x) = dtG R (t, x, y = 0; 0, 0, 0)…”
mentioning
confidence: 99%